The Role of Islamic Religious Education Teachers in Developing Educators with Integrity and Noble Character - Andriani, Selfi; Mutathahirin, Mutathahirin; Nurhaliza, Pioni; Hilmi, Hilmi (Suluah Pasaman, 2025)
Being an Islamic religious education teacher is a job that carries a great deal of responsibility, especially in shaping the personality and character of students, not to mention its influence on colleagues, namely other educators. This study aims to examine the role of Islamic religious education teachers in shaping educators with integrity and noble character through a literature review approach. The literature review method was chosen to analyze various sources of literature, journals, and previous studies relevant to the topic of the role of Islamic religious education teachers in character building. By analyzing previous theories and research results, this study found that Islamic education teachers play a strategic role in the internalization of Islamic values, such as honesty, responsibility, and patience, which directly influence the strengthening of educators' character. Islamic education teachers are not only teachers but also role models in everyday life who are able to motivate educators to develop high ethical and moral attitudes. This study highlights the importance of the Islamic values approach in shaping the character of educators, thereby supporting the creation of a meaningful and high-quality educational environment. The results of this study are expected to serve as a reference for educators and policy makers in maximizing the role of Islamic education teachers as agents of character building.